1992
DOI: 10.1021/ac00030a009
|View full text |Cite
|
Sign up to set email alerts
|

The predominant role of swelling-induced modulus changes of the sorbent phase in determining the responses of polymer-coated surface acoustic wave vapor sensors

Abstract: The sorption of vapors by fluoropotyol, poly(epichlorohydrln), and poly(lsobutytene) Is examined by gas-liquid chromatography (GLC), and these results are compared with the responses of surface acoustic wave (SAW) vapor sensors coated with the same polymers. The sensor responses exceed those which can be attributed to gravimetric effects, Indicating that the SAW devices are responding to some other change In the coating properties. A model Is developed to estimate the effect of polymer swelling on SAW sensor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
206
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(216 citation statements)
references
References 32 publications
7
206
3
Order By: Relevance
“…17 Changes in the viscoelastic properties of the chemically sensitive or waveguiding layer may also contribute to the observed frequency shift when guided SH-SAW sensors are exposed to aqueous analytes. This effect has been noted in gas-phase SAW sensor studies where the viscoelastic contribution to the observed frequency shift was defined in terms of swelling-induced modulus changes 18,19 as, accessed by following the link in the citation at the bottom of the page.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…17 Changes in the viscoelastic properties of the chemically sensitive or waveguiding layer may also contribute to the observed frequency shift when guided SH-SAW sensors are exposed to aqueous analytes. This effect has been noted in gas-phase SAW sensor studies where the viscoelastic contribution to the observed frequency shift was defined in terms of swelling-induced modulus changes 18,19 as, accessed by following the link in the citation at the bottom of the page.…”
mentioning
confidence: 85%
“…The contribution of mass loading to the sensor response is well accepted in this field while the contribution of the viscoelastic property of polymer coating is still under investigation, even in gasphase sensors. 18,19,[25][26][27] Unfortunately, results in gas phase cannot be totally adapted or used to explain liquid-phase responses. For example, ongoing work in liquid-phase sensing has also shown that for a rubbery polymer such as PDMS viscoelasticity changes can clearly dominate sensor response.…”
Section: Mass Loading and Viscoelastic Contributions To Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…The Phase behavior of polymer solutions are of extreme importance for the development of in several polymer processing and many polymers are produced in solution [1], [2]. The polymer devolatilization and other polymeric membrane separation processes [3], recovery of organic vapors from waste-air streams using a polymeric membrane [4], and pervaporation [5] may be have a few residual solvents.…”
Section: Introductionmentioning
confidence: 99%